Illusory Body Ownership Affects the Cortical Response to Vicarious Somatosensation. (8th July 2021) - Pamplona, Gustavo S P; Salgado, Julio A D; Staempfli, Philipp; Seifritz, Erich; Gassert, Roger; Ionta, Silvio
Abstract: Fundamental human feelings such as body ownership ("this" body is "my" body) and vicariousness (first-person-like experience of events occurring to others) are based on multisensory integration. Behavioral links between body ownership and vicariousness have been shown, but the neural underpinnings remain largely unexplored. To fill this gap, we investigated the neural effects of altered body ownership on vicarious somatosensation. While recording functional brain imaging data, first, we altered participants' body ownership by robotically delivering tactile stimulations ("tactile" stroking) in synchrony or not with videos of a virtual hand being brushed ("visual" stroking). Then, we manipulated vicarious somatosensation by showing videos of the virtual hand being touched by a syringe's plunger (touch) or needle (pain). Only after the alteration of body ownership (synchronous visuo-tactile stroking) and specifically during late epochs of vicarious somatosensation, vicarious pain was associated with lower activation in premotor and anterior cingulate cortices with respect to vicarious touch. At the methodological level, the present study highlights the importance of the neural response's temporal evolution. At the theoretical level, it shows that the higher-level (cognitive) impact of a lower-level (sensory) body-related processing (visuo-tactile) is not limited to body ownership but also extends to other psychological body-related domains, such as vicarious somatosensation.